Effective Parental Leadership in Guiding Children Memorizing the Qur'an - Nur Zazin; Salman Basri; Ummu Khumairah Husin Lubis (Al-Qalam Institue, 2025)
This study aims to determine the effective parental leadership model in guiding children who have memorized 30 juz at the Tahfidz House. The research method used was a qualitative case study approach, involving observation, in-depth interviews with parents and children who have memorized the Qur'an, and analysis of supporting documents. The results of the study indicate that a parental leadership model that prioritizes an open communication approach, loving discipline, and spiritual motivation is very influential in the success of children memorizing 30 juz of the Qur'an. In addition, active parental involvement in the learning process and emotional support are also essential factors. The implications of this study emphasize the importance of strengthening the role of parents as spiritual leaders and primary motivators in building a conducive home environment for children to memorize successfully.